Mirror Syndrome assocciated with Patau Syndrome: A Case Report - Pais, Ana Sofia; Areia, Ana Luísa Fialho Amaral de; Franco, Sofia Margarida Perienes; Fonseca, Etelvina Morais Ferreira; Moura, José Paulo Achando Silva (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Mirror syndrome is an unusual pathological condition in which maternal edema in pregnancy is seen in association with severe fetal and/or placental hydrops. The disease can be life-threatening for both the mother and the fetus. The pathogenesis is poorly understood, and may be confused with preeclampsia, even though distinguishing features can be identified. We report a rare case of mirror syndrome with maternal pulmonary edema associated with fetal hydrops due to Patau syndrome.
Keywords: pregnancy; hydrops fetalis; pulmonary edema; trisomy 13 syndrome